The handbook of European fixed income securities - Fabozzi, Frank J.; Choudhry, Moorad (Frank J. Fabozzi series., 2004)
A well-rounded guide for those interested in European financial markets. With the advent of the euro and formation of the European Union, financial markets on this continent are slowly beginning to gain momentum. Individuals searching for information on these markets have come up empty-until now. The Handbook of European Fixed Income Markets is the first book written on this burgeoning market. It contains extensive, in-depth coverage of every aspect of the current European fixed income markets and their derivatives. This comprehensive resource includes both a qualitative approach to products.